Implementasi Akuntansi Sederhana dan Literasi Akuntansi terhadap Sustainability Finansial dengan Moderasi Tingkat Pendidikan - Yudi Febriansyah; Amir Hamzah; Iman Teguh (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
Abstract This study aims to analyze the effect of simple accounting implementation and accounting literacy on the financial sustainability of housewives, and to examine the moderating role of education level in this relationship. The research is motivated by the low adoption of financial recording and limited accounting literacy among housewives, which negatively impacts household financial resilience. The study employs a quantitative approach with a descriptive-verificative method. A total of 247 housewives in Kuningan Regency were selected using a random sampling technique. Data were collected via questionnaires and analyzed using SmartPLS 4.0. The results reveal that both simple accounting practices and accounting literacy have a positive and significant effect on financial sustainability. Moreover, education level shows a significant direct effect and also serves as a moderator that strengthens the relationship between accounting practices and financial sustainability. These findings emphasize the critical role of education and accounting skills in enhancing household financial resilience. The practical implication of this study suggests the need for community-based accounting training programs for housewives to support sustainable household financial management. Keywords: simple accounting, accounting literacy, financial sustainability, housewives, education